PENERAPAN GAME BASED LEARNING DALAM MATERI PEMBELAJARAN K3 DENGAN GAME “DISCOVER HAZARD IN THE WORKPLACE” - Kuswoyo, Deni; Elviana, Elviana; Latif, Antina (Universitas Budi Luhur, 2024)
Safety education in schools is usually taught conventionally by teachers, but this learning method is currently not appropriate to students' development and interests. The improvement of learning media with recreations is an elective to today's learning for understudies since they can learn utilizing a ubiquitous demonstrate (learning anyplace) without time and put imperatives. Game development research uses the Game Development Life Cycle (GDLC) method with a game based learning approach. The test results for this game use an alpha testing and beta testing approach, where there are no errors or obstacles in the game. The results of this research produced a game with the title